Cash-for-work and food-for-work programmes' role in household resilience to food insecurity in southern Ethiopia. Issue 8 (16th November 2020) - Abebe, Gezahegn
ABSTRACT: The article uses survey and interview data from Boricha District in southern Ethiopia to assess the challenges and prospects of cash-for-work and food-for-work programmes for building households' resilience to food insecurity. The findings show that the programmes are of little use for improving farmers' food security. The analysis suggests that a human rights-based approach to social protection is needed as it sees social protection as an inherent social right, rather than as charity for beneficiaries. This approach is the correct direction to strengthen vulnerable groups' capacity to respond to the social, political, economic, and environmental drivers of food insecurity and thus alleviate poverty and inequality.